Transovarial Transmission of a Plant Virus Is Mediated by Vitellogenin of Its Insect Vector - Huo, Yan; Liu, Wenwen; Zhang, Fujie; Chen, Xiaoying; Li, Li; Liu, Qifei; Zhou, Yijun; Wei, Taiyun; Fang, Rongxiang; Wang, Xifeng (PLoS pathogens, 2014)
Most plant viruses are transmitted by hemipteroid insects. Some viruses can be transmitted from female parent to offspring usually through eggs, but the mechanism of this transovarial transmission remains unclear. Rice stripe virus (RSV), a Tenuivirus, transmitted mainly by the small brown planthopper (Laodelphax striatellus), is also spread to the offspring through the eggs. Here, we used the RSV-planthopper system as a model to investigate the mechanism of transovarial transmission and demonstrated the central role of vitellogenin (Vg) of L. striatellus in the process of virus transmission into the eggs. Our data showed Vg can bind to pc3 in vivo and in vitro and colocalize in the germarium. RSV filamentous ribonucleoprotein particles (RNPs) only accumulated in the terminal filaments and pedicel areas prior to Vg expression and was not present in the germarium until Vg was expressed, where RSV RNPs and Vg had colocalized. Observations by immunoelectron microscopy (IEM) also indicated that these two proteins colocalized in nurse cells. Knockdown of Vg expression due to RNA interference resulted in inhibition of the invasion of ovarioles by RSV. Together, the data obtained indicated that RSV RNPs may enter the nurse cell of the germarium via endocytosis through binding with Vg. Finally, the virus enters the oocytes through nutritive cords, using the same route as for Vg transport. Our results show that the Vg of L. striatellus played a critical role in transovarial transmission of RSV and shows how viruses can use existing transovarial transportation systems in insect vectors for their own purposes.